Re-Establishing the Esthetics of Incisors in Patients with Molar Incisor Hypomineralisation - Silva Júnior, Jefferson Pires; Mendonça, Rafael Pinto [UNESP]; Rocha, Rafael Santos [UNESP]; Rios, Daniela; Bresciani, Eduardo [UNESP] (Karger Publishers, 2024)
The awareness of molar incisor hypomineralisation (MIH) has led to its increased clinical detection, consequently drawing more attention to its associated complications. This text offers an overview of the esthetic management of anterior teeth affected by MIH, a condition characterized by enamel defects that present significant cosmetic challenges. The focus is on the clinical presentation of MIH characteristics, considering the depth of lesions and the clinical aspects, and the treatment protocols available, despite a lack of extensive scientific evidence. To the best of the current scientific knowledge, the text evaluates the potential of minimally invasive procedures, as well as the use of traditional composite resin techniques and their possible combinations, highlighting the critical role of esthetic considerations for the impacted anterior teeth. The chapter is augmented with five illustrative clinical cases that display the practical application of these treatment approaches. These examples articulate the clinical decision-making process and personalized restorative strategies, aiming to balance function with enhanced esthetic results. The described cases act as a road-map for clinicians tackling the complexities of MIH treatment in the context of limited empirical evidence, providing insights into achieving both satisfactory and esthetically pleasing outcomes for patients suffering from this condition.